MANAJEMEN KURIKULUM PENDIDIKAN KARAKTER BERBASIS NILAI-NILAI KEAGAMAAN - Ubaidillah, Aan Eko Khusni (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2018)
Education requires good management including Islamic education. The main aspect of the success of national education is the curriculum. Therefore, good management (management / regulation) of a curriculum is a necessity in achieving educational goals. Curriculum management is a system of managing a curriculum that is cooperative, comprehensive, systemic, and systematic in order to realize the achievement of curriculum objectives. Character education should be carried out in planned and measurable stages and have a strong foundation, especially religious-based values